Electromagnetic and heated pulse laser on wave propagation during electrons and holes excitation processes in a rotator semiconductor medium - S. M. Abo-Dahab; Doaa M. Salah; Hanan S. Gafel; A. M. Abd-Alla; M. A. Abdelhafez (Scientific Reports)
Abstract This study focuses on intricate interplay between electrons and holes and generating a Hall current and its impact on the coupled behavior of thermal, mechanical, and electronic fields in a semiconductor thermoelastic medium. The model indeed considers the motion of microscopic particles (charge carriers such as electrons and holes) by coupling their behaviour with thermal and elastic fields. The process of optical-elastic-thermal-diffusion (OETD) is taken into account when a material is subjected to rotation, time, high electromagnetic fields, and laser pulses. Significant data on the existence of new and enhanced waves in many technological and geophysical applications can be obtained from wave propagation in a thermos-diffusion elastic material. Photoelastic and photoelectronic deformations are accounted for, especially when hall currents impact the semiconductor due to magnetic field pressure. To solve the non-dimensional coupled equations, Lame’s potential and normal mode analysis were employed to simplify the fundamental equations that describe the system in 2-D. Graphical representations of numerically simulated results using MATHEMATICA software highlight the influence of hall current (magnetic field), laser pulse, rotation and time on the results, with a focus on silicon (Si) material. Finding of the current study is that the effect of electromagnetic field on wave propagation heated by pulsed laser during the excitation processes of electrons and holes in a rotator semiconductor medium.